Burden and trends of arrhythmias in hypertrophic cardiomyopathy and its impact of mortality and resource utilization. Issue 4 (29th June 2019) - Tripathi, Byomesh; Khan, Safi; Arora, Shilpkumar; Kumar, Varun; Naraparaju, Vamsidhar; Lahewala, Sopan; Sharma, Purnima; Atti, Varunsiri; Jain, Varun; Shah, Mahek; Patel, Brijesh; Ram, Pradhum; et al.
Abstract: Background: Hypertrophic cardiomyopathy (HCM) accounts for significant morbidity and mortality worldwide. Arrhythmias are considered the main cause of mortality, however, there is paucity of data relating to trends of arrhythmia and associated outcomes in HCM patients. Methods: Nationwide Inpatient Sample from 2003 to 2014 was analyzed. HCM related hospitalizations were identified using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD9‐CM) code 425.1 and 425.11 in all diagnosis fields. Results: Overall, there was an increase in number of hospitalizations related to arrhythmias among HCM patients from 7784 in 2003 to 8380 in 2014 (relative increase 10.5%, P  < 0.001). The increase was most significant in patients ≥ 80 years and those with higher comorbidity burden. Atrial fibrillation (AF) was the most frequently occurring arrhythmia however atrial flutter (AFL) witnessed the highest rise during the study period. In general, there was a down trend in mortality with the greatest reduction occurring in patients with ventricular fibrillation/flutter (VF/VFL). The mean length of stay was higher if patients had arrhythmia, which led to increased cost of care from $16105 in 2003 to $19310 in 2014 (relative increase 22.9%, P  < 0.001). Conclusion: There is overall decline in HCM related hospitalizations but rise in hospitalization among HCM patients with arrhythmias. HCM with arrhythmia accounts for significant inpatient mortality coupled with prolonged hospital stay and increased cost of care. However, there is an encouraging downtrend in the mortality most likely because of improved clinical practice, cardiac screening and primary and secondary prevention strategies.